Flexed-knee gait in children with cerebral palsy: A 10-year follow-up study. (November 2013) - Haumont, Thierry; Church, Chris; Hager, Shaun; Cornes, Maria Julia; Poljak, Dijana; Lennon, Nancy; Henley, John; Taylor, Daveda; Niiler, Tim; Miller, Freeman
Abstract: Background: While several studies have evaluated the short-term effectiveness of conservative and surgical treatment of flexed-knee gait in children with cerebral palsy (CP), few have explored the long-term outcomes using gait analysis. The purpose of this study was to examine, through gait analysis, the 10-year outcomes of flexed-knee gait in children with CP. Methods: Ninety-seven children with spastic CP who walked with a flexed-knee gait underwent two gait evaluations [age 6.1 ± 2.1 and 16.2 ± 2.3 years, Gross Motor Function Classification System (GMFCS) I (12), II (45), III (37), IV (3)]. Limbs with knee flexion at initial contact >15° were considered walking with a flexed-knee gait and were included in the study ( n = 185). Kinematic data were collected using an eight-camera motion analysis system (Motion Analysis, Santa Rosa, CA). Surgical and therapeutic interventions were not controlled. Results: A comparison between the two gait studies showed an overall improvement in gait at 10 years follow-up. Significant improvements were seen in knee flexion at initial contact, Gait Deviation Index (GDI), Gross Motor Function Measure (GMFM), and gait speed ( P < 0.01 for all). Outcome was also evaluated based on the severity of flexed-knee gait at the initial visit, with functional skills and overall gait (GDI) improving in all groups ( P < 0.01 for all). The group with a severe flexed-knee gait exhibited the most improvement, while subjects with a mild flexed-knee improved the least. Conclusions: Children at a specialty hospital whose orthopedic care included gait analysis and multi-level surgery showed improvement of flexed-knee gait and gross motor function over a 10-year course, regardless of the initial severity.